Beyond the Ear, the Hidden Threat of Paecilomyces Neuro-Otological Infection: A Case Report - Jing Hern Khoo; Izny Hafiz Zainon; Hafizah Husna Johari; Ida Sadja’ah Sachlin (Journal of International Advanced Otology)
Background: Paecilomyces spp. are thermo-tolerant fungi found in decaying vegetables and soil. They can cause ocular, cutaneous, and miscellaneous infections. In otorhinolaryngology, most infections occur in the paranasal sinuses, while otological infection is uncommon.